The Relationship between Attitudes, Workload, and Work Environment and Midwives’ Performance in Early Detection of High-Risk Pregnancy - Ar-Rohman, Bilqis; Permata, Annisa Devi; Handayani, Titi Purwitasari (Genius Journal, 2026)
Introduction: The high rates of maternal and neonatal mortality remain a major global health challenge, with non-obstetric complications and hypertensive disorders being the dominant causes of death. Although the Maternal and Child Health (MCH) Handbook is used as a monitoring instrument, incomplete data recording by healthcare providers continues to hinder the early detection of high-risk conditions. Objective: The purpose of this study is to determine the relationship between attitudes, workloads, and work environment to the performance of midwives in filling out the KIA book in the early detection of high-risk pregnant women in the Tarogong Kidul sub-district area in 2024. Method: The research method is quantitative research, with a descriptive analytical method with a Cross Sectional design. The sample of this research is a midwife in the working area of Tarogong Kidul Garut District with a sampling technique using total sampling. The data analysis used used the Chi square statistical test. Results: The study showed that workload and work environment can affect the work performance of midwives with a sig value (p=<0.05) in filling out the KIA book in the early detection of high-risk pregnant women. Conclusion: this study shows that workload and work environment are significantly related to midwife's performance in filling out the KIA book.